Influence of residence time and helium addition in the ammonia formation on tungsten walls in N2H2 glow discharge plasmas. (August 2017) - de Castro, A.; Alegre, D.; Tabarés, F.L.
Highlights: Changes in the residence time for nitrogen ( τ N 2 τ N2 ) from 25 to 50 ms do not change significantly the ammonia formation yields but a higher value of 100 ms increases them up to a 25%. Helium addition in the Glow Discharge Plasma (0–8%) enhances the ammonia formation up to a 45%. To explain these results, three possible effects related with the presence of Helium in the plasma have been studied: decreasing pumping speed, increasing electron temperature and modification of the tungsten surface and associated chemistry. Among these studied effects, the changes in the surface N-H recombination and the increasing effective surface area induced by the helium bombardment seems to be the key factor that could explain the experimental results Abstract: The influence of the residence time for the active species and of the helium addition to the plasma in the ammonia formation in N2 H2 (He) Glow Discharge plasmas has been studied using differential pumped mass spectrometry. Three different residence times for the N2 molecule were studied: 25, 50 and 100 ms. Other experiments scanning the helium plasma content (0–8%) were performed with a residence time of 100 ms. While no difference in the ammonia formation yields was found between the cases of 25 ms and 50 ms, the ammonia yields were increased by a 25% in the case of 100 ms. Additionally, an increasing helium plasma content enhances the ammonia formation yields up to 45%. Three different effects induced by the presence of helium in the plasma were analyzed: effects in mass spectrometry measurements, changes in the electron temperature and modification of the surface chemistry. The analyzes pointed out to an improved NH recombination on tungsten walls induced by helium presence as the key factor that could explain the higher ammonia yields experimentally found for the highest helium content in the plasma.